Persistence and immunogenicity of chemically attenuated blood stage Plasmodium falciparum in Aotus monkeys. Issue 9 (August 2016) - De, Sai Lata; Stanisic, Danielle I.; van Breda, Karin; Bellete, Bernadette; Harris, Ivor; McCallum, Fiona; Edstein, Michael D.; Good, Michael F
Graphical abstract: Highlights: Evaluation of persistence and immunogenicity of chemically attenuated Plasmodium falciparum (CAPs) in non-human primates. Parasite DNA was detected in the blood of the CAP-inoculated monkeys for up to 8 days. CD8 + T cell response to cultured live P. falciparum was seen in the CAP-inoculated monkeys. Plasmodium falciparum CAPs can induce T cell responses and as such supports undertaking a human study. Abstract: Malaria is a disease caused by a protozoan of the Plasmodium genus and results in 0.5–0.7 million deaths per year. Increasing drug resistance of the parasite and insecticide resistance of mosquitoes necessitate alternative control measures. Numerous vaccine candidates have been identified but none have been able to induce robust, long-lived protection when evaluated in malaria endemic regions. Rodent studies have demonstrated that chemically attenuated blood stage parasites can persist at sub-patent levels and induce homologous and heterologous protection against malaria. Parasite-specific cellular responses were detected, with protection dependent on CD4+ T cells. To investigate this vaccine approach for Plasmodium falciparum, we characterised the persistence and immunogenicity of chemically attenuated P. falciparum FVO strain parasites (CAPs) in non-splenectomised Aotus nancymaae monkeys following administration of a single dose. Control monkeys received either normal red blood cells or wild-type parasites followed by drug treatment. Chemical attenuation was performed using tafuramycin A, which irreversibly binds to DNA. CAPs were detected in the peripheral blood for up to 2 days following inoculation as determined by thick blood smears, and for up to 8 days as determined by quantitative PCR. Parasite-specific IgG was not detected in monkeys that received CAPs; however, in vitro parasite-specific T cell proliferation was observed. Following challenge, the CAP monkeys developed an infection; however, one CAP monkey and the infection and drug-cure monkeys showed partial or complete resistance. These experiments lay the groundwork for further assessment of CAPs as a potential vaccine against malaria.